Study of the effect of active pharmaceutical ingredients of various classes of BCS on the parameters of thermosensitive systems based on poloxamers - E.O. Bakhrushina; A.I. Khodenok; V.S. Pyzhov; P.G. Solomatina; N.B. Demina; T.V. Korochkina; I.I. Krasnyuk (Saudi Pharmaceutical Journal, 2023)
Introduction: The development of thermosensitive in situ systems has become widespread and prospective due to the optimal parameters of the phase transition - in the temperature range from room to physiological. Those properties can provide thermosensitive polymers, for example, poloxamers - as the most common.It is worth noting that the addition of active pharmaceutical ingredients (APIs) changes the parameters of in situ systems, but no systematic study of the effect of APIs has been conducted. The aim of this work was to develop a systematic approach to studying the effect of APIs on the in situ rheological properties of poloxamer compositions. Materials and methods: The biopharmaceutical classification system (BCS) was chosen as the basis. Accordingly, the following APIs were selected for the experiment: BCS class I - lidocaine hydrochloride and ketorolac tromethamine, class II - ibuprofen and diclofenac, class III - pyridoxine hydrochloride and ribavirin, class IV - furosemide and abiraterone. To create thermoreversible compositions, previously studied for stability combinations of poloxamer 407, poloxamer 188 and PEG 1500 were used.At the stage of preparation of experimental samples formulations with APIs of classes II and IV of BCS were excluded, since the solubilizing ability of poloxamers is not enough to obtain stable combined complexes. Results: In the course of the work, the following results were obtained: BCS class I APIs significantly reduced the phase transition temperature of the matrix of poloxamers 407 and 188, while the addition of PEG 1500 eliminated the effect of APIs on gels; BCS class III APIs practically did not affect the rheological properties of the studied combinations; the phase transition temperature of the gel based on poloxamer 407 did not change with the addition of Class I and Class III APIs.Nevertheless, the obtained results made it possible to reveal the regular behavior of in situ complexes of poloxamer matrices depending on the class of BCS of the API. Further research is required.